PERENCANAAN DINDING PENAHAN BADAN JALAN TIPE GRAVITASI STUDI KASUS : PENINGKATAN JALAN HARUKU-OMA RUAS JALAN ABORU-HARUKU - Yusuf, Densya; Hutubessy, Vector R. R; Soumokil, Musper David (Journal Agregate, 2024)
The condition of the road in Haruku Village experienced a landslide on the road to Oma Village which was 15 meters long and the landslide depth was 5 meters. The retaining wall on the road body is a construction structure built to stabilize the pressure on the road body and certain soil conditions. In general, retaining walls are used in natural slope areas and artificial slope areas as well as areas that are prone to landslides. The aim of this planning is to obtain the distribution of lateral pressure that works and the stability of the road body retaining walls that are safe against shear forces, overturning forces and collapse in the bearing capacity of the road body in Haruku Village, Haruku Island District, Central Maluku Regency. The methods used are the Rankine method regarding active earth pressure and passive earth pressure on road retaining walls and the Terzaghi method regarding soil bearing capacity. The results of the calculation of the lateral pressure distribution acting on the retaining walls of the Haruku Village road are the active earth pressure distribution value, namely the flat active soil coefficient value for flat soil (Ka), namely 0.33, the active soil pressure value for non-cohesive soil (Pa), namely 81.72 kN and the value The passive earth pressure coefficient for flat soil (Kp) is 3. The passive earth pressure coefficient for non-cohesive soil (Pp) is 42.36 kN. From the results of the safety factor calculation, the value of wall stability against shear is 2.80>1.5 (Safe), the wall stability value against overturning is 2.70>1.5 (Safe) and the safety factor against collapse of the bearing capacity is 15.67> 3 (Safe).